The Relationship Between Leg Muscle Explosive Power and Strength with Dribbling Skills in Football Games - Habibulloh, Muhammad; Permono, Purwono Sidik (Journal Physical Health Recreation (JPHR), 2025)
This research endeavors to analyze the extent to which lower limb explosive power and leg muscle strength influence dribbling proficiency among 13 to 15 year old football players at SSB Bhineka Gubug FC. The methodology in this study aligns with the principles of quantitative descriptive research. The study population includes all male players of SSB Bhineka Gubug FC aged 13-15 years, with a research sample of 22 players selected using the total sampling technique. The data subjected to correlation analysis using SPSS version 26, with the significance level set at 0.05. Based on the outcomesvof this analysis, the study yields the following conclusion : (1) A significant contribution of leg muscle explosive power to ball dribbling skills was obsserved ; (2) Leg muscle strength contributes significantly to ball dribbling skills ; (3) Leg muscle explosive power and leg muscle strength together contribute significantly to ball dribbling skills, with both variables explaining 83.6% of the variation in ball dribbling skills.